The Yin Yang Role of Nitric Oxide in Prostate Cancer - Soni, Yash (Am J Mens Health, 2020)
Nitric oxide (NO) is a ubiquitous signaling molecule in the human body with well-known roles in many different processes and organ systems. In cancer, the two-concentrations hypothesis of NO has dictated that low levels of NO are cancer promoting, while high levels of NO are protective against cancer. Although prostate cancer is a hormonally driven malignancy, research has been shifting away from androgen-responsive epithelial cells and evolving to focus on NO therapies, the tumor microenvironment (TME), and inflammation. NO is reported to be able to inhibit activity of the androgen receptor. This may prevent prostate growth, but low levels of NO could conversely select for castration-resistant prostate cells, creating an aggressive cancer phenotype. At high levels, nitrosative stress created from NO overproduction can be protective against prostate neoplasia. In this review, we discuss development and possibilities of NO-based therapies for prostate cancer.